(untitled) (CIPEEX, 2025)
INTRODUCTION: Colorectal cancer is one of the most prevalent neoplasms, with high morbidity and mortality, and feasible screening through simple tests, such as the fecal occult blood test (FOBT) and, when indicated, colonoscopy. Despite the availability of these tests in primary care, adherence remains low. Understanding the limiting factors is essential to expand early diagnosis and reduce mortality. OBJECTIVE: To analyze the factors related to population adherence to colorectal cancer screening within the scope of primary health care in Brazil. METHODOLOGY: An integrative literature review was carried out in the SciELO, Google Scholar, and PubMed databases in July 2025. The following DeCS descriptors were used: “Colorectal Neoplasms”, “Neoplasias Colorretais”, “Mass Screening”, “Rastreamento de Doenças”, “Primary Health Care”, and “Atenção Primária à Saúde”. Original articles published between 2020 and 2025, in Portuguese or English, with free access to the full text, were included. Reviews and studies outside the primary care context were excluded. Six articles were selected after critical reading. RESULTS: The studies identified the following main barriers: lack of population awareness about the importance of the exam, absence of medical recommendation, limitations in access to colonoscopy after a positive result, embarrassment regarding the stool test, and logistical difficulties in sample collection and return. Actions such as home delivery of the FOBT, educational campaigns, active search, team training, and the work of community health agents proved effective, significantly increasing adherence, surpassing 80% in some contexts. CONCLUSION: Adherence to colorectal cancer screening in primary care in Brazil remains low, influenced by cultural, institutional, and operational factors. This review shows that simple interventions, such as community education, professional training, and flow definition, expand the participation of the target population. It reinforces the importance of organizing the line of care in the SUS and of primary care as the gateway for early diagnosis and mortality reduction.